EJA: o lugar da escola na vida dos jovens - Reis, Maria Conceição dos (2017)
The present study sought an understanding of the place of the school in the life of young people who attend a CIEJA (Integrated Center for Youth and Adult Education). The EJA is not part of the recent history of our country, it has been configured since our colonization. CIEJA is one of the modalities of the EJA, an institution that serves people who have not been able to follow the course of a regular school. The 2013 census points to 3.7 million young people enrolled in the EJA, it serves to "plug" a social hole, seeking to fix something that did not work as provided by law. The young people in our research are mostly poor and black and are statistically among those who die the most for violent reasons and are generally neglected. For this study a psychoeducational intervention was carried out with a group of young people from CIEJA during the second half of 2015 and another reflective meeting with another group of young people in August 2016. Allowing these young people to be heard enables a systematization of knowledge, Of the impressions and expectations of these young people when seeking the CIEJA, promoting new looks about their reality, demystifying preconceived ideas and labels naturalizing these students as failures and inferiors. These youngsters come to school the necessary way to build a life project, CIEJA being one of the last possibilities to be able to complete their formal education, since they were systematically expelled from regular education. The CIEJA presented here is democratic, but it is in the midst of a public policy that has not yet found its way, and tends more and more to lose itself in the neglect of a needy and marginalized population. A democratic school is one that provides students with the skills necessary to intervene later in the spaces where their social and individual lives decide. Denying this right is perpetuating an unjust and unequal society